Moxibustion Improves Chronic Heart Failure by Inhibiting Autophagy and Inflammation via Upregulation of mTOR Expression. (2nd February 2021) - Li, Qingling; Wang, Wei; Ma, Qiang; Xia, Ran; Gao, Bing; Zhu, Guoqi; Wang, Jing
Abstract : How moxibustion improves chronic heart failure is extremely complex and still unclear. This study aimed to explore whether moxibustion inhibits autophagy and reduces inflammation by regulating mTOR expression to induce myocardial protective effects and alleviate symptoms associated with chronic heart failure. Echocardiography was used to detect cardiac function and cardiac structure of rats, including heart rate (HR), left atrium diameter (LA), left ventricular diameter (LV), left ventricular posterior wall (LVPW), interventricular septum (IVS), ejection fraction (EF), and fractional shortening (FS). BNP and NT-pro BNP levels were measured by enzyme-linked immunosorbent assay (ELISA). Autophagy-associated protein (ATG) genes and mTOR were detected by PCR. The expression of mTOR and phosphorylated-mTOR was detected through western blotting of proteins from myocardial tissue samples. The left ventricular inflammatory response was detected by immunohistochemistry and included ICAM-1, VCAM-1, MMP-2, and MMP-9 expression. The relationship between autophagy and inflammation was analyzed by correlation analysis. The results from echocardiography and ELISA showed that moxibustion could significantly improve heart function and structure. Western blot and PCR results showed that moxibustion treatment elevated mTOR expression. Further, moxibustion could inhibit autophagy and regulate the expression of key autophagy-related genes, including Vps34, ATG3, ATG5, ATG7, ATG12, and ATG13. By contrast, rapamycin could partially reduce the effects of moxibustion. Immunohistochemistry results indicated that moxibustion could reduce myocardial inflammation. Moreover, there was a positive correlation between autophagy and inflammation. Moxibustion can protect cardiac function in rats with heart failure, possibly inhibiting excessive autophagy of cardiomyocytes and reducing inflammatory reactions through the elevation of mTOR expression.